Means to Enhance Operating Efficiency of the Concrete Mixer Trucks with the Purpose of Highly-Homogeneous Concrete Mix Preparation - Emeljanova, Inga; Anishchenko, Anna; Dobrohodova, Olga (International Journal of Engineering and Technology, 2018)
Option shall be considered to create concrete mixer trucks for preparation not only of high-flow but also of low-slump and dry type concrete mixes. With these aims it is offered to transfer operation to the cascade mode being characterised by combination of two principles on concrete mix preparation: gravitational and forced action.Design solution of the concrete mixer truck of gravitational-forced operation with spiral-blade shaft has allowed to liquidate available free places in the drum. The dependencies for calculation and arrangement of mix particles motion in the workspace of the machine drum are provided.Â  Graphic performance confirms the absence of free zones.There is description of dependency for determining the homogeneity degree obtained on the basis of the experimental investigation findings.Â Â
Keywords: concrete mixer truck of gravitational-forced operation; spiral-blade shaft; degree of homogeneity; degree of homogeneity.